2015
DOI: 10.1039/c5cc00331h
|View full text |Cite
|
Sign up to set email alerts
|

Remarkably stable chelating bis-N-heterocyclic carbene adducts of phosphorus(i) cations

Abstract: A convenient one-pot synthesis of chelating bis-N-heterocyclic carbene-ligated P(I) salts is described. The solid state structures of these remarkably stable phosphamethine cyanine dyes with various N-alkyl groups and counter-anions are reported, and initial reactivity results are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
66
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(75 citation statements)
references
References 29 publications
9
66
0
Order By: Relevance
“…The dative bondingm odel for compounds 1P and 4P has been corroborated through computational and reactivity studies, demonstrating 4P as aP I transfer reagent. [53][54][55][56][57][58][59] Can the same charge transfer that was observed in 1Ge, 1GeCl,a nd 2OTf be spectroscopically verified in 1P and 4P?…”
Section: Resultsmentioning
confidence: 76%
“…The dative bondingm odel for compounds 1P and 4P has been corroborated through computational and reactivity studies, demonstrating 4P as aP I transfer reagent. [53][54][55][56][57][58][59] Can the same charge transfer that was observed in 1Ge, 1GeCl,a nd 2OTf be spectroscopically verified in 1P and 4P?…”
Section: Resultsmentioning
confidence: 76%
“…Our group has developed an efficient route to phosphamethine cyanines (which can be considered as NHC‐stabilised phosphorus(I) cations when delocalisation of the π‐type lone pair on phosphorus is minimised) involving P + transfer from a triphosphenium salt . We also showed that one of these cations, [L] + , may bind one or two equivalents of gold(I) chloride .…”
Section: Introductionmentioning
confidence: 99%
“…Schmidpeter had observed early on that cyanide ions displace 1,2‐bis(diphenylphosphino)ethane (dppe) from a triphosphenium cation to form DCP anions in solution using 31 P NMR spectroscopy . Indeed, nucleophilic substitution of the phosphine ligands from triphosphenium cations has been used by our group as a conceptually simple and practical method for the generation of new or useful univalent phosphorus containing molecules and oligomers . Using these results as a basis, we investigated the reactions of [dppeP][Br] and commercial cyanide sources like [K][CN], [Na][CN] and [ n Bu 4 N][CN] in the hopes of finding a safe, straightforward method of synthesizing and isolating DCP salts.…”
Section: Methodsmentioning
confidence: 99%